pergeseran fungsi seni grafis dari karya seni murni menjadi karya seni terapan - Nova Agung Prasetya; Setyo Budi (Texture:Art and Culture Journal, 2020)
abstractthe purpose of this research is to understand the changes that occur in graphic art. especially the shift in fuction from graphic art from the dysnatic era to the present era.the development of pure graphic artwork into applied work is based on the need of the widdercommunity that are processed and integrated together with fuctional product.reference from graphic art, especially for high print techniques than began with woodenboard, to gouge, as it expanded into the media of rubber, screen, hardoard, stone, andmetal. The research is more focused and processing graphic arts to become an appliedart that can add economic value to artist. these changes will be reviewed by the author.And what is the cause of the change of graphic art to applied art